Proposed new interior design of Asian Food Channel Studio (M) for Alice George Communications Sdn. Bhd. at The Red Bungalow, No 151 & 153 Jalan Ampang, 50450 Ampang, Kuala Lumpur / Muna Hanina Mawardi - Mawardi, Muna Hanina (Faculty of Architecture, Planning and Surveying, 2011)
Final student in Diploma Architecture needs to come out with project report in order to understand the whole final project in every aspects started from basic level to final presantatation. The final project is proposed new design scheme of Asian Food Channel studio (M) for Alice George Communication Sdn. Bhd. At the red bungalow, 151 & 153 Jalan Ampang, 50450 Ampang, Kuala Lumpur. Asian Food Channel is a food programming which is being show on Astro, channel 703. Every of the avid followers are intend to pay a visit to the studio. The first and only AFC studio was opened in December 2009 at Orchad Central, Singapore. Comprising of a retail store, events location and a filming studio, the space is intended to provide a touch point for its viewers. The co-finder of the AFC studio, Maria Brown and Hian Goh are in the process of expanding their business. Malaysia is the best choice to proposed the new AFC studio for there are no AFC studio yet proposed in Malaysia. Viewer of AFC is encreasing everyday, hence, this is the best opportunity to boost our tourism sector cause this can be our tourist attraction. Moreover, we all know Malaysian is in the risk of obesity and other disease cause by unhealthy eating habit, AFC studio had come with food programming which will help viewer understand more on healthy eating habit. According to New Straits Time, Wednesday. 10. 2010, Health Minister Datuk Seri Liow Tiong Lai said obesity is becoming the major health issue with the number of obese people almost tripling in the past 15 years from four per cent in 1996 to 14 per cent in 2010. It is important for all Malaysians to get more knowledge on healthy eating habit. This project is being proposed according to the projects goal and client requirement. The main objective is to design a studio with a suitable concept in order to give the viewer a chance in experiencing the studio. The process to complete this project is being held according to the design stage, starting with project brief, research and analysis, till lastly proposal design. In conclusion this proposal is the new design scheme which make the design process need to be research in every aspect require.